2021
DOI: 10.1007/s11686-021-00405-4
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the Spotted-Tail Quoll, Dasyurus maculatus, as a Definitive Host for the Pentastomid Linguatula sp. in Australia

Abstract: Purpose Specimens of a pentastomid, identified as a nymphal Linguatula serrata, have previously been reported from the nasal cavity of the endangered Australian marsupial, the spotted-tail quoll, Dasyurus maculatus. These specimens were made available for morphological and molecular characterisation to confirm their species identity. Methods Specimens were examined by light microscopy. Molecular sequencing attempts were unsuccessful. Results Examination showed that the specimens were adult pentastomes of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Recently we showed that a number of introduced parasites entered the country and now are established in Australia, infecting native and protected species. For example, the European tongue worm, Linguatula serrata , was found in red-necked wallabies and spotted-tail quolls ( Barton et al, 2020 ; Barton et al, 2021 ), and anchor worm, Lernaea cyprinacea , was found in wild Murray cod ( Zhu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently we showed that a number of introduced parasites entered the country and now are established in Australia, infecting native and protected species. For example, the European tongue worm, Linguatula serrata , was found in red-necked wallabies and spotted-tail quolls ( Barton et al, 2020 ; Barton et al, 2021 ), and anchor worm, Lernaea cyprinacea , was found in wild Murray cod ( Zhu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%